Gone in a flash: manipulation of audiovisual temporal integration using transcranial magnetic stimulation - Hamilton, Roy; Wiener, Martin; Drebing, Daniel; Coslett, Branch (Frontiers in Psychology, 2013)
While converging evidence implicates the right inferior parietal lobule in audiovisual integration, its role has not been fully elucidated by direct manipulation of cortical activity. Replicating and extending an experiment initially reported by Kamke et al. (2012), we employed the sound-induced flash illusion, in which a single visual flash, when accompanied by two auditory tones, is misperceived as multiple flashes (Wilson, 1987; Shams et al., 2000). Slow repetitive (1 Hz) TMS administered to the right angular gyrus, but not the right supramarginal gyrus, induced a transient decrease in the Peak Perceived Flashes (PPF), reflecting reduced susceptibility to the illusion. This finding independently confirms that perturbation of networks involved in multisensory integration can result in a more veridical representation of asynchronous auditory and visual events and that cross-modal integration is an active process in which the objective is the identification of a meaningful constellation of inputs, at times at the expense of accuracy.